ISSUES OF PRIVATE ENTREPRENEURSHIP DEVELOPMENT IN THE SPHERE OF POVERTY REDUCTION AND INCREASED WELLBEING OF THE POPULATION - Khushvakov , Anvar (THE INNOVATION ECONOMY, 2023)
This article presents the concept of poverty, its definitions, poverty and the theoretical foundations of its reduction. The article gives ideas about the study of the category of poverty and the definition of the factors that form poverty, and the main directions for reducing poverty.